Balinese Culture-Based Digital Comic Learning Media for Strengthening Pancasila Student Profiles for Elementary School Students - Putri, Komang Putri Cahyani; Suarjana, I Made; Bayu, Gede Wira (MIMBAR PGSD Undiksha, 2023)
The current problem is the decline in student character and learning media that does not yet apply Balinese culture. This research aims to develop digital comic media based on Balinese culture to strengthen the Pancasila Student Profile of grade IV elementary school students. This research uses the ADDIE development model. The method used is a questionnaire. The research subject is digital comic media based on Balinese culture, while the research object is the design, validity of the media developed, teacher responses and student responses to digital comic media. The data analysis technique used is qualitative and quantitative descriptive analysis. The results of the research are that the design consists of a comic cover, comic opening, comic content, comic cover, and in the form of a PDF file. The validity of digital comic learning media was declared valid and appropriate based on the percentage of material content experts 98%, media experts 95%, and design experts 98% (very good). The fourth grade elementary school teacher's response based on practitioner tests obtained a percentage of 100% (very good) so it is suitable for use in learning activities. Student responses based on individual trials obtained a percentage of 98.7% and small group trials 97.7% (very good). It was concluded that digital comic media based on Balinese culture is suitable for use in learning. 7% and small group trials 97.7% (very good). It was concluded that digital comic media based on Balinese culture is suitable for use in learning. 7% and small group trials 97.7% (very good). It was concluded that digital comic media based on Balinese culture is suitable for use in learning.